2008
DOI: 10.1086/588297
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Hepatitis C Virus Infection among Injection Drug Users in the United States, 1994–2004

Abstract: Although regional differences exist, our data suggest that the incidence of HCV infection among injection drug users in the United States decreased from 1994 through 2004.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
125
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(133 citation statements)
references
References 24 publications
8
125
0
Order By: Relevance
“…Sexual variables examined included sexual orientation (75.6 % straight/heterosexual, 11.3 % homosexual, 13.1 % bisexual), number of sexual partners in the past 3 months (median=1, IQR [1][2][3]), lifetime history of STI diagnosis (17.8 %), and exchanging sex for money or drugs in the past 3 months (27.2 %); none of which differed significantly by HCV infection status (all P values90.1; data not shown).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sexual variables examined included sexual orientation (75.6 % straight/heterosexual, 11.3 % homosexual, 13.1 % bisexual), number of sexual partners in the past 3 months (median=1, IQR [1][2][3]), lifetime history of STI diagnosis (17.8 %), and exchanging sex for money or drugs in the past 3 months (27.2 %); none of which differed significantly by HCV infection status (all P values90.1; data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Older age and longer injecting duration could account for the higher upper bounds of these estimates; however, two U.S. studies 8,9 reported finding 33 and 36 % of IDUs under 25 years old were HCV infected and several non-U.S. studies found a much higher prevalence even among IDUs in this age group. 10 In 2007, 48 % of individuals with incident HCV in the U.S. reported injection drug use, which continues to be the leading risk factor for infection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 IDU among young adults has been increasing since the 1990s 6 and studies of young persons who inject drugs (PWID) have found anti-HCV prevalence of 30-70% among PWID depending on frequency and duration of IDU. 2 Many young PWID are unaware of their HCV status, 9 although persons who receive drug treatment or syringe exchange program services are more likely to be aware than those who do not receive these services. 7 PWID have limited access to healthcare and are infrequently tested for anti-HCV using conventional laboratory assays.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, studies have documented that the prevalence of hepatitis C among injection drug users has decreased, though it remains high. [8][9][10] Needle and paraphernalia use and sharing among drug users have decreased since the 1990s as a result of improved awareness and education, and because higher drug purity facilitates snorting rather than injecting. [11][12][13] Receiving a blood transfusion is also a common risk factor, but HCV transmission through transfusion declined as standards for donor deferral and screening improved, especially since US blood banks began using an accurate HCV screening test in 1992.…”
Section: Introductionmentioning
confidence: 99%